Improving Spare Part Storage to Reduce Searching Time by Implementing 5S - Hirawati Oemar; Dea Legina Ayu Kusumah; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2022)
PT XYZ is a company in publishing, printing, security printing, and general trading. This company uses many large machines to carry out the production process so the spare parts used to support the machine are many types. A large number of types of spare parts is a problem for the company because the storage of spare parts in the company has not been neatly arranged, there is no data collection for incoming and outgoing spare parts, and old and new spare parts are not separated, spare parts are not arranged according to type, there are no special marks on the storage area, and there is spare parts packaging waste in the storage area. This causes technicians to have difficulty when looking for spare parts and causes waste of movement. This study aims to improve the spare parts storage area by minimizing movement waste so that technicians can easily find spare parts. An Analysis of spare parts storage was carried out using a process flow chart and improvements with the application of the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). The application of the 5S method to the spare parts storage area at PT XYZ can regulate the work environment and minimize the time for taking spare parts from 218 minutes to 159 minutes.